The Risk of Using Inductive Risk to Challenge the Value-Free Ideal. Issue 4 (October 2016) - de Melo-Martín, Inmaculada; Intemann, Kristen
Abstract : The argument from inductive risk has been embraced by many as a successful account of the role of values in science that challenges the value-free ideal. We argue that it is not obvious that the argument from inductive risk actually undermines the value-free ideal. This is because the inductive risk argument endorses an assumption held by proponents of the value-free ideal: that contextual values never play an appropriate role in determining evidence. We show that challenging the value-free ideal ultimately requires rejecting this assumption.